Mortality trends among Indian Medical Association member doctors in India (2018-2023): Implications of the COVID-19 pandemic - Nirmal Jyotsana; Ashish Trivedi; Niraj Pandit; Harsh Audichya; Yagna Pandit (​​​One Health Bulletin, 2025)
Objective: To analyze mortality trends among Indian Medical Association (IMA) member doctors in India from 2018 to 2023 and to assess the impact of the COVID-19 pandemic. Methods: This was a cross-sectional study based on secondary data analysis of the doctors’ mortality reported to and published by the IMA as a part of their National Social Security Scheme. Yearly membership details and death records of the member doctors from 2018 to 2023 were accessed from the published annual reports of IMA-National Social Security Scheme and analyzed. Results: The number of deaths reported annually among IMA member doctors increased from 896 out of a total population of 15862 in 2018 to 1579 out of 16253 in 2023. The calculated death rate among member doctors was 56.5 per 1000 in 2018 and 97.1 per 1000 in 2023. The mean age at death among doctors during the COVID period (64.9±9.0) was significantly lower than that during pre-COVID (67.3±11.1) and post-COVID (66.1±8.5) periods. Conclusions: This study shows a rising number of deaths and death rate among member doctors of IMA from 2018 to 2023. The average age at death during the study period ranged from 64 to 67 years, with a significant decline of approximately 2.4 years during the COVID-19 period.